Ethical issues in using camera phone / Fara Ai'ni Jamal - Jamal, Fara Ai'ni (2004)
This research is purposely done to determine whether camera phone abuse can occur among FTMSK societies. It is also to determine whether camera phone abuse may cause information theft, privacy issues and violation the law. In addition, this research also makes a comparison between students and lecturers. Besides, the researcher will propose an ethical guideline on proper usage of camera phone. Questionnaires were distributed to the FTMSK societies. The researcher also conducted an interview sessions with the academic staffs in FTMSK to gain more information regarding camera phone usage. On the whole, it can be said that FTMSK societies do not abuse the use of camera phone. However, there are minority of them who still have the tendency to abuse camera phone usage. Therefore, an ethical guideline has been proposed as a preparation for Malaysian to use camera phone properly.